2018
DOI: 10.1177/2042098618770620
|View full text |Cite
|
Sign up to set email alerts
|

Does the 5-HT1A rs6295 polymorphism influence the safety and efficacy of citalopram therapy in the oldest old?

Abstract: Major depressive disorder (MDD) in older people is a relatively common, yet hard to treat problem. In this study, we aimed to establish if a single nucleotide polymorphism in the 5-HT receptor gene (rs6295) determines antidepressant response in patients aged > 80 years (the oldest old) with MDD. Nineteen patients aged at least 80 years with a new diagnosis of MDD were monitored for response to citalopram 20 mg daily over 4 weeks and genotyped for the rs6295 allele. Both a frequentist and Bayesian analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…22 In small studies of the elderly, the C allele was protective against depressed mood in healthy athletes compared to nonathletes (n = 55 v. 58) 84 and enhanced remission to 4-week citalopram treatment in people recently diagnosed with depression (n = 19). 85 In addition, the G allele was inversely correlated with parasympathetic tone, which was associated with reduced anxiety in healthy participants (n = 1141). 86 Thus, the rs6295 G allele associates with depression and anxiety phenotypes, while the C allele may be protective.…”
Section: Htr1a Rs6295 and Phenotypic/brain Network Alterationsmentioning
confidence: 98%
“…22 In small studies of the elderly, the C allele was protective against depressed mood in healthy athletes compared to nonathletes (n = 55 v. 58) 84 and enhanced remission to 4-week citalopram treatment in people recently diagnosed with depression (n = 19). 85 In addition, the G allele was inversely correlated with parasympathetic tone, which was associated with reduced anxiety in healthy participants (n = 1141). 86 Thus, the rs6295 G allele associates with depression and anxiety phenotypes, while the C allele may be protective.…”
Section: Htr1a Rs6295 and Phenotypic/brain Network Alterationsmentioning
confidence: 98%
“…A meta‐analysis showed that the G allele was present in 50% of Caucasians but only in 21% of Asians, but only the Asians studies showed a significant association of the polymorphism with treatment response (Kato & Serretti, 2010). Another study showed an association of the C/C genotype and response to treatment with Citalopram in geriatric patients (Scutt et al., 2018). While there are a lot of unexplained inconsistencies between studies, some studies (Lemonde et al., 2004; Serretti et al., 2004) have made a strong argument regarding the contribution of the polymorphism to pharmacogenetics of antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with 65 patients, the results showed that the G allel carriers of 5HT1A receptors might be more resistant to antidepressant treatment (15). In a study on 19 geriatric patients using citalopram, remission rates were found different in diverse 5HT1A genotypes (16). On the other hand in other clinical studies, no relationship was found with SSRI treatment success and 5HT1A receptor polymorphism (17,18).…”
Section: Pharmacogenetics Of Selective Serotonin Reuptake Inhibitors ...mentioning
confidence: 93%